Answer:
x^4-x^3-5x^2-3x
Step-by-step explanation
Use the FOIL Method or factor.
Answer:
The answer would be A
Step-by-step explanation:
Both congruent sides are pairs
Answer:
0.258819045...
Step-by-step explanation:
just plug it into a calculator
Answer:
, option B
Step-by-step explanation:
Complex numbers:
The most important relation that involves complex numbers is given by:
![i^2 = -1](https://tex.z-dn.net/?f=i%5E2%20%3D%20-1)
Solving a quadratic equation:
Given a second order polynomial expressed by the following equation:
.
This polynomial has roots
such that
, given by the following formulas:
![x_{1} = \frac{-b + \sqrt{\bigtriangleup}}{2*a}](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D%20%5Cfrac%7B-b%20%2B%20%5Csqrt%7B%5Cbigtriangleup%7D%7D%7B2%2Aa%7D)
![x_{2} = \frac{-b - \sqrt{\bigtriangleup}}{2*a}](https://tex.z-dn.net/?f=x_%7B2%7D%20%3D%20%5Cfrac%7B-b%20-%20%5Csqrt%7B%5Cbigtriangleup%7D%7D%7B2%2Aa%7D)
![\bigtriangleup = b^{2} - 4ac](https://tex.z-dn.net/?f=%5Cbigtriangleup%20%3D%20b%5E%7B2%7D%20-%204ac)
In this question:
The solutions are:
![x_1 = 1 - 3i, x_2 = 1 + 3i](https://tex.z-dn.net/?f=x_1%20%3D%201%20-%203i%2C%20x_2%20%3D%201%20%2B%203i)
We have to find the polynomial. All option have
. So
![(x - (1 - 3i))(x - (1 + 3i)) = x^2 - x(1 + 3i) - x(1 - 3i) + (1 - 3i)(1 + 3i) = x^2 - x -3ix - x + 3ix + 1^2 - (3i^2) = x^2 - 2x + 1 - 9i^2 = x^2 - 2x + 1 - 9(-1) = x^2 - 2x + 10](https://tex.z-dn.net/?f=%28x%20-%20%281%20-%203i%29%29%28x%20-%20%281%20%2B%203i%29%29%20%3D%20x%5E2%20-%20x%281%20%2B%203i%29%20-%20x%281%20-%203i%29%20%2B%20%281%20-%203i%29%281%20%2B%203i%29%20%3D%20x%5E2%20-%20x%20-3ix%20-%20x%20%2B%203ix%20%2B%201%5E2%20-%20%283i%5E2%29%20%3D%20x%5E2%20-%202x%20%2B%201%20-%209i%5E2%20%3D%20x%5E2%20-%202x%20%2B%201%20-%209%28-1%29%20%3D%20x%5E2%20-%202x%20%2B%2010)
The correct answer is given by option b.